The Process of Visibility of Women with Disabilities: Diference and Profile - Diaz Balado, Alicia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2012)
In the last decades, Feminist Gender Studies have raised the invisibility of women as well as the later recognition of feminine specificity. The main european and american universities have considered disability process from the occidental culture, which is jointly affected. The observance of the women with disabilities circunstances is a relevant item, whereas women have been central subject in the Gender Studies analysis. This article describes the different gender theories contributions and recognizes a variety of publications and its relevance. Current contribution tries to come close to the reflection on difference´s women with disabilities.